Strategic Management Methodology to Improve Sustainability in Companies Real Estate Housing Medians in Lima - Muñoz, Ana Lucía Chaiña; Guzmán, Carlos Noriega Niño de; Pimentel, Johnny Félix Farfán (International Journal of Membrane Science and Technology, 2023)
In order to develop a strategic management technique to improve sustainability in medium-sized companies housing real estate agencies, the following investigation was carried out in the city of Lima. Both a qualitative and quantitative research approach was used to conduct the study. The sample was made up of 80 senior company managers real estate. In this way, the present study made it possible to elucidate characteristics in its current situation with respect to finance, commerce and marketing of the management business of real estate SMEs in Lima and when analyzing the results it was possible note that almost all companies in different areas of the economic sector use similar strategies, which means that the application of a strategy will have a high probability of being successful binding on any other SME real estate company . In the same order of ideas, it is specified that the proposed strategic management model was addressed at the financial, operations, commercial and marketing levels. Likewise, it is highlighted that it was developed in the stage’s transversal studies of preliminary studies, design, construction and deployment, and post-sale, which without a doubt allows a comprehensive approach adapted to the needs observed in companies addressed to ensure their sustainability.